Women's Participation in Governance: A Quick Fix to Development Constraints in Sub-Saharan Africa? - Isayomi, Abiodun Samuel; Omodunbi, Olumide Olumuyiwa; Ogunleye, Akin George; Olabiyi, Kehinde Ajike; Olaniyan, Samson Olajide (Universitas Airlangga, 2024)
The inhuman socioeconomic repercussions of corruption and bad governance inherent in successive male-dominated governments have generated agitation for increased women's participation in governance. Primarily, this agitation is based on the premise that women are less inclined to corruption, which is a major impediment to good governance. Given the notoriety of these two impediments to development, this study aims to investigate the relationship between women's participation in governance, corruption, and quality of governance in sub-Saharan Africa from 1996 to 2021. This study analyzed annual panel data of four sub-Saharan African countries using the autoregressive distributed lag model and the Granger causality test. Governance quality was proxied by government effectiveness, while women's participation in governance and corruption were proxied by the number of women in government positions and control of corruption, respectively. Economic development and institutional quality were used as control variables. The findings revealed negative main and interaction effects of women's participation in governance and corruption on governance quality, unidirectional causality from corruption to women's participation in governance and from governance quality to women's participation in governance, and bidirectional causality between corruption and governance quality. Quantitative increases in women's participation in governance and corruption exacerbates governance quality. Women's ability to participate in governance is determined by the prevalence of corruption in previous years. Anticorruption campaigns that focused on women's participation in governance often result in reductions in corruption insufficient for improvement of governance quality. Corruption and bad governance are mutually reinforcing. Governance quality determines women's participation in governance. To minimize corruption and bad governance, sub-Saharan African countries should shift their focus away from merely increasing the number of women in government positions to building strong institutions capable of creating a meritocratic political and socioeconomic environment in which selfless women and men have equal chances of being elected or appointed to public offices.